Employee Engagement at Shafira Tour and Travel - Nisa, Nova Khoirun; Hakim, Ahmad Khairul (Fakultas Dakwah dan Komunikasi Universitas Islam Negeri Walisongo Semarang, 2021)
Employee engagement is employee awareness in collaborating with colleagues to improve performance and be involved in the company's success. The purpose of this study is to describe the efforts of Shafira Tour and Travel in building employee engagement and describe the factors that influence employee engagement at Shafira Tour and Travel. In this study, researchers used qualitative research methods with descriptive research. Data collection techniques used to obtain Shafira Tour and Travel information are interview, observation, and documentation techniques. The results ilustrate that Shafira Tour and Travel strives for twelve ways to build employee engagement, namely the recruitment process, job training, simulation and product knowledge, leader’s roles, organizational roles, creating two-way communication, development opportunities, complementing facilities, meet the needs of employees, build a good and strong culture, hold annual outings, and pay attention to employees. The efforts made by Shafira Tour and Travel are quite complex so that they can meet the values and expectations of employees. The efforts made by Shafira Tour and Travel are the factors that affect employee engagement